Public Relations Management in Improving the Image and Performance of Educational Institutions: Strategies, Challenges, and Implications - Karmilah, Lilah; Kartini, Eni; Kusuma, Zakia Nur Aras Wiguna; Rostika, Neneng; Iskandar, Sofyan (Papanda Publisher, 2025)
Public relations management plays a strategic role in building and maintaining a positive image and improving the performance of educational institutions in the midst of evolving social dynamics. This article aims to analyze the public relations strategies that can be effectively implemented, the challenges faced in their implementation, and the long-term implications for the reputation and sustainability of educational institutions. Through a qualitative-descriptive approach and literature study, it is found that well-managed public relations can strengthen internal and external communication, build public trust, and support the achievement of the institution's vision and mission. However, challenges such as limited resources, internal resistance, and changes in communication technology demand continuous adaptation and innovation. The implications of effective public relations management not only impact on public perception, but also on increasing participation, the quality of education services and the competitiveness of the institution. Therefore, strengthening the capacity of public relations is one of the strategic keys in the management of modern educational institutions.